Understanding the impact of tenure status on the overall life satisfaction of BNG housing subsidy beneficiaries - Beckley, Frederick (My University, 2020)
The high levels of in migration to the Gauteng province has led to an increase in the demand for housing in post-Apartheid South Africa. The government has faced numerous housing and socio-economic challenges with regards to the urban poor. Tracking the magnitude of state-provided housing in its mandate to better the well-being of citizens is of significance at various scales. Programmes such as the Reconstruction and Development Programme (RDP) have provided housing for the urban poor in order to better the well-being of recipients. For the purposes of the study the betterment of one’s life is considered to be the overall satisfaction an individual has with their life. The overall perception of an individual’s well-being is influenced by various predictor variables within different spheres of life, which include social, political and economic domains. Therefore, understanding how of tenure status affects RDP housing recipients perception of their overall well-being is the main focus of the study. This paper defines tenure status as the legal ownership of land occupied by South African citizens (Cambridge, 2019). The definition poses various questions but it accommodates the dynamics of land transfer in South African communities. Overall life satisfaction is defined in two ways: the degree to which an individual is healthy, comfortable, and able to participate in or enjoy life events (Jenkinson, 2016); and a sociological category designating all possibilities offered to the individual by society in order to organise their existence based on their own needs and desires (Bucur, 2017). Various studies refer to the term quality of life and overall life satisfaction interchangeably and this study will do the same. The data used to predict overall life satisfaction is obtained from the GCRO’s (Gauteng City-Region Observatory) Quality of Life survey conducted bi-annually. The study area considered is the Gauteng province and excludes the other areas included in the Gauteng City-Region. The multinomial logistic regression model is used to determine the probable effects of the predictors of overall life satisfaction. The five quality of life surveys have been considered in order to trace the significant variables across time. The results of the five models run include subjective and objective domains. Tenure status is considered to impact the overall life satisfaction of individuals; nonetheless the model identifies an insignificant impact of RDP housing on overall life satisfaction
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements of the Master’s Degree in Development Planning, 2020